2022
DOI: 10.3892/etm.2022.11648
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomarkers for doxorubicin‑induced cardiac injury in rats

Abstract: Drug-induced cardiotoxicity is a leading cause of failure in drug development and predicting its occurrence in non-clinical studies is the primary preventive measure. The present study aimed to evaluate the changes in biomarkers during acute and chronic myocardial injury induced by doxorubicin (DOX) in rats. A rat model of acute myocardial injury was established through a single-dose, intraperitoneal injection of DOX (40 mg/kg), the changes in biomarkers were measured at 2, 4, 8 and 24 h after administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Change in troponin levels is a characteristic marker for cardiac damage and its rise in serum is widely used in clinical practice to diagnose cardiac injury. Previous studies have shown that troponin T was reduced in cardiac tissue, probably because it was released into the circulation after myocardial damage [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Change in troponin levels is a characteristic marker for cardiac damage and its rise in serum is widely used in clinical practice to diagnose cardiac injury. Previous studies have shown that troponin T was reduced in cardiac tissue, probably because it was released into the circulation after myocardial damage [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…DOX administration significantly increased cTnI (p < 0.05) which was consistent with the other studies. 44,45 Interestingly, co-treatment with AP extract drastically reduced cTnI level (p < 0.05) (Figure 4). BNP belongs to a group of naturally occurring peptides known as natriuretic peptides (NPs).…”
Section: Effect Of Ap On Troponin and Bnp Levelmentioning
confidence: 93%
“…This release of troponins into the blood allows for their detection and measurement in a blood test, serving as a valuable indicator of heart damage. 44 In this study, the level of cTnI was measured in serum. DOX administration significantly increased cTnI (p < 0.05) which was consistent with the other studies.…”
Section: Effect Of Ap On Troponin and Bnp Levelmentioning
confidence: 99%